Surface State Treatment of Carbon Dots Using Sulphur Dioxide Isotherm - L. Natrayan; Dhinakaran Veeman; Pravin P. Patil; V. Swamy Nadh; P. Balamurugan; Muse Degefe Chewaka (Adsorption Science & Technology)
Low toxicity carbon dots are combating the disadvantages of quantum dots. The carbon dots find their applications in many fields due to their versatile nature. Four different types of carbon dots are present, according to the way of manufacturing and application the type is chosen. The water-soluble characteristics of carbon dots help them be involved in biomedicine applications. The optical properties of the carbon dots find applications as drug delivery, biosensors, LED, etc. The properties like fluorescence, photoluminescence, and phosphorescence are found in the carbon dots. The carbon dots occupy the tiny spot that exhibits different optical properties on excitation. The carbon dots excitation is mainly due to surface states. The characterization of surface states is very complex. The surface states contain the core structure of carbon and oxygen functional groups on the surfaces. The anions and cations formed from functional groups on excitation will recombine themselves. The functional groups are usually carboxyl and hydroxyl groups. The Π-collaborative network of the electronic structure contains many quantization levels which help the carbon dots to produce different wavelengths adapting to different applications. Due to the interference of the structure of the carbon dots, the entire property will vary. Doping of heteroatom methods is employed to enhance the fluorescence, and photoluminescence property carried out. They used N, S, P, and B heteroatoms singly and in combination to doping carbon dots. Here, the paper proposes the sulphur dioxide adsorption technique to enhance the optical properties of the carbon dots. The proposed method shows 8.5% efficiency in relative fluorescence intensity and 8% efficiency in terms of photoluminescence intensity.